2013
DOI: 10.1021/jp3056366
|View full text |Cite
|
Sign up to set email alerts
|

CO Adsorption on a Mixed-Valence Ruthenium Metal–Organic Framework Studied by UHV-FTIR Spectroscopy and DFT Calculations

Abstract: The mixed-valence metal−organic framework [Ru 3 II,III -(btc) 2 Cl 1.5 ] (Ru-MOF) was synthesized by the controlled SBU approach and characterized by combined powder XRD, XPS, and FTIR methods. The interaction of CO molecules with Ru-MOF was studied by a novel instrumentation for ultra-high-vacuum (UHV) FTIR spectroscopy. The high-quality IR data demonstrate the presence of two different CO species within the framework: a strongly bonded CO showing a low-lying band at 2137 cm −1 and a second CO species at 2171… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 63 publications
3
51
0
Order By: Relevance
“…Noei et al, in a recent study combining IR absorption spectroscopy and Density Functional Theory (DFT), showed that CO adsorbed at different sites in a mixed valence ruthenium (II,III) analogue to HKUST-1 (Cu 3 btc 2 ) can be assigned, and the binding strength determined. [41] Gaseous CO stretch mode is located at 2143 cm À1 , and adsorption of CO on metal cations via electrostatic interaction results in a blue shift of the CO stretch mode with respect to the gas phase. This blue shift is caused by the polarization of the CO molecule.…”
Section: Co Interactionsmentioning
confidence: 97%
“…Noei et al, in a recent study combining IR absorption spectroscopy and Density Functional Theory (DFT), showed that CO adsorbed at different sites in a mixed valence ruthenium (II,III) analogue to HKUST-1 (Cu 3 btc 2 ) can be assigned, and the binding strength determined. [41] Gaseous CO stretch mode is located at 2143 cm À1 , and adsorption of CO on metal cations via electrostatic interaction results in a blue shift of the CO stretch mode with respect to the gas phase. This blue shift is caused by the polarization of the CO molecule.…”
Section: Co Interactionsmentioning
confidence: 97%
“…As these sites were created by the incorporation of the 5‐OH‐ip linkers in 1 a – 1 d , we selected 1 c and 1 d as two representative samples that both exhibit high degrees of 5‐OH‐ip incorporation but quite different contents of Ru 2+ and Ru δ + . As shown in Figure , on CO 2 dosing for both the parent Ru‐MOF and Ru‐DEMOF 1 c , an intense and broad IR band appears at 2336 cm −1 , which is assigned to the asymmetric stretching mode ν as (COO) of physisorbed CO 2 binding linearly at various Ru sites . The weak band at 2273 cm −1 indicates the presence of a minority CO 2 species originating probably from the adsorption of a small amount of 13 CO 2 with an expected isotopic shift of 1.03.…”
Section: Resultsmentioning
confidence: 92%
“…showed that [Cu 3 (btc) 2 ] (BTC=1,3,5‐benzenetricarboxylate) can be doped with different concentrations of low‐coordinating linkers, such as 5‐cyano‐1,3‐benzenedicarboxylate (CYDC), which leads to a particular variety of MTV‐MOF in which additional Cu + sites and mesopores are formed as compared with the parent, undoped [Cu 3 (btc) 2 ] material. This has also been shown to be the case for its ruthenium analogue, with which very active olefin hydrogenation and dimerization catalysts could be synthesized …”
Section: Introductionmentioning
confidence: 84%
“…Consequently, the redox properties of the coordinatively unsaturated sites (CUSs), if already present, can be altered (e.g., reduced oxidation states) . Representative examples of this strategy for the HKUST‐1 topology (a MOF consisting of copper with 1,3,5‐benzenetricarboxylate linkers) have been reported by Baiker and Fischer and their co‐workers, in which the presence of mixed‐valence paddle‐wheel units with Cu 2+ /Cu + centers were observed. Indeed, Fang et al.…”
Section: Introductionmentioning
confidence: 99%